Comparison of Medication Administration Errors (MAEs) and order returns between two wards in a tertiary government hospital with and without a modified Unit Dose Drug Distribution System (UDDDS) - Aloc, Angelica R. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Objectives: The study aimed to compare the frequency of medication administration errors (MAEs) and order returns between two wards of a tertiary government hospital with and without UDDDS.
Methods: A retrospective, cross-sectional study was conducted by reviewing records for medication administration history of randomly selected patient medication charts from admissions during October 2016 in Wards 1 (with UDDDS) and 3 (without UDDDS) as well as all order returns processed for these wards from October to December 2016.
Results: A total of 40 charts from each ward were reviewed. One thousand twenty-one MAEs (39.8%) in Ward 1 and 779 MAEs (31.2%) in Ward 3 were counted. A significant difference in the frequency of errors (X 2= 40.3843, p < 0.001, α = 0.05) was found between Ward 1 and 3. Moreover, a higher number of returns from Ward 1 (n = 206), corresponding to 1,282 line items, was found when compared to Ward 3 returns (n = 8), corresponding to 33 line items.
Conclusion: Ward 1 had a higher frequency of MAEs compared to Ward 3 in our study. However, it cannot be generalized that UDDDS leads to an increase in MAEs due to the presence of several biases. In terms of the order returns, the ward with UDDDS was observed to have higher number of order returns. UDDDS may have increased the monitoring of drugs, leading to more returns.
Available to the general public.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2017.
Keywords: Maturino, Vielka Alexandria W; Tuzon, Ryan Joseph C; Ruamero, Edwin C.,​; Medication errors; Hospitals--Drug distribution systems--Unit-dose.